2013
DOI: 10.1159/000349977
|View full text |Cite
|
Sign up to set email alerts
|

Distal Pancreatectomy Utilizing a Flexible Stapler Closure Eliminates the Risk of Pancreas-Related Factors for Postoperative Pancreatic Fistula

Abstract: Objectives: To identify the risk factors for clinically relevant pancreatic fistula after distal pancreatectomy with a flexible cartridge stapler, TL60. Methods: Forty consecutive patients who underwent a distal pancreatectomy by the TL60 stapler were retrospectively reviewed in association with postoperative complications. Results: The overall morbidity rate was 43% (17 patients), and mortality was null. Pancreatic fistula was the most frequent postoperative complication, seen in 11 patients (27.5%): grade A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 74 publications
0
8
1
Order By: Relevance
“…Lower levels of albumin are believed to be more likely to result in pancreatic leakage. In contrast, there was no significant difference in the level of the preoperative albumin between the two groups in our work, nor was it in the work of Kawabata [35]. We found that patients with higher DA are more prone to develop a POPF, and statistical analysis of the DA showed a difference between these 2 groups.…”
Section: Discussioncontrasting
confidence: 87%
“…Lower levels of albumin are believed to be more likely to result in pancreatic leakage. In contrast, there was no significant difference in the level of the preoperative albumin between the two groups in our work, nor was it in the work of Kawabata [35]. We found that patients with higher DA are more prone to develop a POPF, and statistical analysis of the DA showed a difference between these 2 groups.…”
Section: Discussioncontrasting
confidence: 87%
“…Several authors investigated the risk factors for POPF after DP with stapler closure [9,11,[22][23][24][25][26][27]. Most of them reported that a thick pancreas was a risk factor for POPF [9,11,22,24,25,27].…”
Section: The Risk Factors For Popf In Procedures Involving Stapler CLmentioning
confidence: 99%
“…Although several techniques have been advocated to close the stump of the remnant pancreas, such as hand-sewn closure, stapler closure, ultrasonic dissection, seromuscular patches, and pancreaticoenteric anastomosis, it remains unclear which of these techniques is optimal [6][7][8][9][10]. Currently, stapler and hand-sewn closures are widely performed as standard techniques [11,12]. Although several studies have reported that stapler closure contributes to a reduction in PF after DP [13][14][15][16], a randomized clinical trial to test the efficacy of stapler closure in DP in comparison with hand-sewn closure (DISPACT trial) revealed that stapler closure did not significantly reduce the incidence of PF [17].…”
Section: Introductionmentioning
confidence: 99%